THE PROBLEM OF THE ANNUNCIATION OF TRUTHS AND FARABI's HERITAGE IN THE HISTORY OF MATHEMATICS - Sartabanov , Ж.; Shaukenbaeva , А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
When talking about mathematics and its history in modern national schools, teachers use literature written during the Soviet era. In those literatures, while acknowledging that the first mathematical data came from the Babylonians and Egyptians, they write that the formation of the science of mathematics should be attributed not to the ancient Greeks, but also not to the Babylonians-Egyptians. The Greeks, who conquered the Egyptians, compared the Babylonians to the Egyptians. Mathematical science was an important branch of civilization in ancient times. Although its information is set forth in one national language, it is known to be the common spiritual wealth of the neighboring ancient peoples surrounding this nation. Because the owners of this wealth are the peoples of this region. In Greek literature there is no mention of the peoples who settled in Babylonian and Egyptian countries, nor of the sages of the non-Greek nations. The worldly and spiritual Babylonians of the country of Bodan are depicted in the pure Greek world. All the wealth was given to Pythagoras and Euclid, and the rest was related to historical truths. The same situation occurred in the history of the medieval period. The mathematical and scientific wealth of the developed Arab civilization was transmitted to the European world in dead Latin. Asian nations and rulers are not mentioned, with the exception of Al-Khorezmi. On the other hand, it is known that the names of European nations and scholars are widely used in the literature. This is a colonial approach to spiritual space. In this regard, we draw attention to the fact that this approach is still very popular and is gaining distribution. The article is devoted to the realistic approach to historical truths in the development of mathematics. In this direction, due attention is paid to the national pride of Al-Farabi's mathematical heritage. In the final part, the problem of inclusion of Farabi's heritage in the textbooks of national schools and measures to promote historical truths was raised. The article is intended primarily for teachers of general education schools. In addition, we believe that it will be useful for physics and mathematics specialists, students and schoolchildren.